Traffic accident criminal act resulting in loss of life at Medan city police office (study of decision number 2698/pid.sus/2018/pn lbp) - Suratman, Suratman; Harahap, Herlina Hanum (Institute Of computer Science (IOCS), 2024)
Traffic accidents are one of the serious problems that threaten the safety of people around the world, including in the jurisdiction of the Medan Police. Every year, thousands of lives are lost and tens of thousands of people are injured due to road accidents. The type of research used in this study is juridical-empirical. Juridical-empirical research is legal research regarding the implementation or enforcement of normative legal provisions directly in every specific legal event that occurs in society. Data collection methods are techniques or methods that can be used by researchers to collect data. Techniques in designating an abstract word that is not manifested in objects, but can only be seen in its use through: questionnaires, interviews, observations, exams (tests), documentation, and others. The crime of